Acetylene-filled pressure broadened short photonic microcells - Hosseini-Zavareh, Sajed (Kansas State University, 2019)
We have developed short acetylene-filled photonic microcells (PMCs’) as optical frequency references in the near infrared region for applications in telecommunication, gas sensing, and metrology. The PMC is a 5-10 cm long hollow-core photonic crystal fiber (HC-PCF) in which the high pressure acetylene gas is confined by sealing the ends of HC-PCF. Acetylene provides 50 strong v₁ + v₃ rotational-vibrational combination bands within 1510-1540 nm which covers the telecommunication window at 1550 nm. PMC’s are a possible replacement for optical frequency references based on gas-filled vapor cells, like the SRM2517a produced by the National Institute of Standards and Technology (NIST). While such cells made practical and accurate frequency calibration readily available, and have been built into measurement equipment and lasers, they are relatively bulky compared to the small footprint now achieved by commercially available lasers. Short PMC’s in particular are compact and robust. In fact, a PMC of similar length would occupy a smaller volume because it has a simple design and it is all-fiber based. Here we demonstrate a novel fabrication technique that is appropriate for making short high pressure optical frequency references using photonic bandgap fibers. Consequently, the aforementioned short PMC has some application of NIST SRM 2517a and can be used for moderate accuracy frequency measurements with fractional accuracy of 7.7×10⁻⁸. By using a tapering technique to seal the microcells, we were able to achieve high transmission efficiency of 80% and moderate accuracy of 10 MHz (1[sigma]) in finding the line center. This approaches that of the NIST SRM 2517a 10 MHz (2[sigma]) accuracy. Using an earlier Q-tipping technique, 37% off-resonant transmission and 5 MHz accuracy were achieved in finding the line center, but a larger etalon-like effect which is approximately 13%, appears on the wings of the optical depth. By using a tapering technique, we were able to decrease the etalon-like effect to less than 1%. In both cases, the microcells could be connectorized, albeit with reduction in off-resonant transmission efficiency, for integration into multi-mode fibers or free-space optical systems. Although contamination is introduced during both fabrication techniques, the P13 PMC line center shift with respect to sub-Doppler center is small according to experimental data. Data show that the PMC line center shift from the sub-Doppler feature for PMC no. 53 with 83% contamination was -15.4 ± 3.3 MHz which is a fractional value of 7.7×10⁻⁸ with respect to the value of the P13 line center of 195 THz. Finally, repeatable measurements show that PMCs are stable in terms of total pressure over approximately one year.
Keywords: Acetylene-filled pressure broadened short photonic microcells